circFLT1 and lncCCPG1 Sponges miR-93 to Regulate the Proliferation and Differentiation of Adipocytes by Promoting lncSLC30A9 Expression - Zihong Kang; Sihuang Zhang; Enhui Jiang; Xinyu Wang; Zhen Wang; Hong Chen; Xianyong Lan (Elsevier, 2020)
Although many circular RNAs (circRNAs) and long non-coding RNAs (lncRNAs) have been discovered in adipocytes, their precise functions and molecular mechanisms remain poorly understood. Based on existing circRNA and lncRNA sequencing data of bovine adipocytes, we screened for the differential expression of circFLT1 and lncCCPG1 in preadipocytes and adipocytes and further analyzed their function and regulation during adipogenesis. The overexpression of circFLT1 and lncCCPG1 together facilitated adipocyte differentiation and suppressed proliferation. Computationally, the RNA hybrid showed that circFLT1 and lncCCPG1 had multiple potential binding sites with miR-93. Additionally, luciferase reporting experiments verified that circFLT1 and lncCCPG1 may interact with miR-93. We also demonstrated that overexpressed miR-93 effectively suppresses the expression of lncSLC30A9. Signaling pathway enrichment analysis, luciferase activity assay, and expression analysis revealed that lncSLC30A9 inhibits proliferation by inhibiting the expression of AKT protein and promotes differentiation by recruiting the FOS protein to the promoter of peroxisome proliferator-activated receptor gamma (PPARG). In sum, our results elucidate the regulatory mechanisms of circFLT1 and lncCCPG1 as miR-93 sponges in bovine adipocytes.